Spinal subarachnoid haemorrhage secondary to spinal rheumatoid vasculitis: a case report - Yeqing Xiao (BMC, 2021)
Abstract Introduction Spinal subarachnoid haemorrhage is extremely rare in cases of subarachnoid haemorrhage and possesses servere characteristics. Additionally, spinal rheumatoid vasculitis is rare for spinal subarachnoid haemorrhage. The pathogenesis is unknown. Case presentation A 52-year-old woman with a 10-year history of seropositive rheumatoid arthritis was managed with leflunomide and celecoxib, and stable low disease activity was achieved. The patient had also been diagnosed with spinal subarachnoid haemorrhage secondary to isolated spinal rheumatoid vasculitis and obtained good therapeutic effects. Conclusion This is the first case to describe spinal subarachnoid haemorrhage secondary to isolated spinal vasculitis in a patient with rheumatoid arthritis, which provides more proof of anomalous neovascularization in the central nervous system in rheumatoid arthritis.